MENINGKATKAN HASIL BELAJAR DENGAN PENGGUNAAN STRATEGI MAKE A MATCH DI SEKOLAH DASAR - Sedya Santosa; Deni Indrawan (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
This action research is motivated by the teaching and learning process of teachers less able to create active and fun learning, the use of methods that are still conventional results in the learning process in the classroom making students feel bored and seem inactive and student learning outcomes below KKM. Classroom action research is the method used in this study. The research subjects were students of class V B MI Al Huda consisting of 37 students. The instruments used were observation, tests and documentation. The results of this study indicate that the implementation of social studies subjects, learning with the make a match strategy can improve student learning activities and outcomes. This can be proven from the results of each cycle designed. In cycle I only 40.54% (15 students completed) with an average of 56.29, cycle II amounted to 56.76% (21 students completed) average score 65.27 and cycle III amounted to 94.60% (35 students completed) with an average of 77.02